(untitled) (Global Journal of Human-Social Science, 2025)
This article aims to analyze the problematic use of practices and outcomes of homeschooling applied in the United States as a parameter for possible results of implementing this educational model in Brazil based on the examples from the Cartilha Educa o Domiciliar um direito tanto dos pais quanto dos filhos highlighting the concepts of cultural and national identity social imaginaries and stereotypes by Hall 1992 Charaudeau 2017 and Amossy 2011 respectively The guiding question is what is the applicability in Brazil of the examples of homeschooling from the United States brought by the Cartilha This article is therefore qualitative research that relies on primary and documentary sources obtained from websites and literature related to the topic The results clarify the infeasibility of comparing the homeschooling model in the United States with what would be the model of this type of education in Brazil given the significant differences in social imaginaries national and cultural identities between the two countries factors that are crucial for educational regulations